HUBUNGAN PENGGUNAAN METODE DEMONSTRASI DENGAN HASIL BELAJAR ILMU PENGETAHUAN ALAM PADA SISWA DI SEKOLAH DASAR NEGERI PASAR KAMIS 1 KECAMATAN KERTAK HANYAR KABUPATEN BANJAR - Tati'ah (Pahlawan Jurnal Pendidikan-Sosial-Budaya, 2020)
This study aims to determine the relationship between the use of demonstration methods with natural science learning outcomes in students at SDN Pasar Kamis 1 Kertak Hanyar District. The method used in this research is quantitative correlation. With a total population of research as many as 164 people and the sampling technique using purposive sampling techniques so that the sample in this study is class III students, amounting to 30 people. Data mining tools used in this study were questionnaire and documentation. Based on data analysis, using the serial correlation formula, it can be concluded that the relationship between the use of demonstration methods and natural science learning outcomes in students at SDN Pasar Kamis 1, Kertak Hanyar District based on hypothesis testing shows rcount = 0.725 lebih besar r table = 0.361 at a significant level of 5% and r count = 0.725 lebih besar r table = 0.463 at a significant level of 1% of N = 30 which means that the alternative hypothesis (Ha) is accepted, and the null hypothesis (H0) is rejected. Based on the results of this study, the suggestions that the researchers want to make are as follows: a) for students, in learning to be more active and not get bored quickly in learning natural science so they can understand the lesson and get satisfying results, b) For teachers, with the existence of this research a teacher to further enhance the creativity of teachers in teaching, because with creativity teachers can use various kinds of media and learning methods that will attract students' attention and make students more active in participating in learning, c) For researchers, this research can make lessons and provision in educating and becoming creative teachers.